Natriuretic Peptides as Biomarkers for Congestive States: The Cardiorenal Divergence - Koratala, Abhilash (Dis Markers, 2017)
Congestion represents the primary reason for hospitalization of patients with heart failure and is associated with adverse outcomes. Fluid overload has been shown to be inadequately addressed in a significant subset of these patients in part due to lack of robust, reliable, and readily available biomarkers for objective assessment and monitoring of therapy. Natriuretic peptides have long been used in this setting, often in conjunction with other assessment tools such as imaging studies. Patients presenting with concomitant cardiac and renal dysfunction represent a unique population with regard to congestion in that the interactions between the heart and the kidney can affect the utility and performance of biomarkers of fluid overload. Herein, we provide an overview of the currently available evidence on the utility of natriuretic peptides in these patients and discuss the clinical conundrum associated with their use in the setting of renal dysfunction. We highlight the potential divergence in the role of natriuretic peptides for assessment of volume status in a subset of patients with renal dysfunction who receive renal replacement therapy and call for future research to elucidate the utility of the biomarkers in this setting.